Management of automation: a survey on systems development strategies, methods and tools - Akkök, Zeynel Abidin (My University, 1993)
unknown
Keywords: BİLİŞİM SİSTEMLERİ; Genel Konular; Sistem belirleme; Sistemler; YAZILIM SİSTEMLERİ_BİLGİSAYARLAR